If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -1(6x + 5) = 3 Reorder the terms: 7x + -1(5 + 6x) = 3 7x + (5 * -1 + 6x * -1) = 3 7x + (-5 + -6x) = 3 Reorder the terms: -5 + 7x + -6x = 3 Combine like terms: 7x + -6x = 1x -5 + 1x = 3 Solving -5 + 1x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 1x = 3 + 5 Combine like terms: -5 + 5 = 0 0 + 1x = 3 + 5 1x = 3 + 5 Combine like terms: 3 + 5 = 8 1x = 8 Divide each side by '1'. x = 8 Simplifying x = 8
| (x/1)=234 | | 2x^2-3xy-35y^2=0 | | x+2x+5x=40 | | j+20= | | 3(2+c)=2(c-1) | | 2-4t+5=15 | | 14x+2y=45 | | 3y-4x=31 | | -x^3-3x^2+4x+12=0 | | (76.5+x)+2x=180 | | 2y+3=3(y-7) | | 4m-8= | | (3x+1)/5=5 | | 20x-5=7+16 | | 2(3x+1)=9x | | 2x-(3x+2)=-7 | | n+(-7)-n= | | g(t)=.75t+3 | | 1.06y-3=8.62 | | 1-2c+12=-3+12-20 | | 25x+70-5x=-20.9 | | 2(3-5x)+2(x-7)=ax+b | | 12-(-u)=19 | | 7b-(2b+7)= | | 2(3+x)=2(3)+2(x) | | 3x-3x=-3x+x-3 | | 8(y-3)=4y-48 | | 1-4b-6b=-9 | | 0.25x+.05(14-x)=.10(-21) | | 1-2(c+6)=-3-4(3-5) | | 0.1x=0.2[x+2] | | -7(x+9)-(2-5x)=-13x |